Natural radioactivity in the prospecting tunnel in Egypt: Dose rate and risk assessment. (October 2021) - Hanfi, M.Y.; Emad, Bahaa M.; Sayyed, M.I.; Khandaker, Mayeen Uddin; Bradley, D.A.
Abstract: Uranium, apparently the most important item of heavy minerals, gains appropriate prominence in nuclear application. The present study divided into two parts is the occupational exposure contributed from the granitic rocks inside the prospecting tunnel as well as the public exposure associated with the extraction of raw materials that may be used in the infrastructure and other their activities. In the present study, the samples are distributed regularly inside various drafts of the prospecting tunnel (El-Missikat). A portable gamma spectrometry was used to detect the content of primordial radionuclides are associated with the granites (each of the sample being of the same geometry approximately). The results showed the mean activity concentrations of 238 U, 232 Th and 40 K are higher than the recommended worldwide average at all monitoring stations in the tunnel. Three radiological indices: radium equivalent (Raeq ) activity, absorbed dose rate (Dair ), outdoor annual effective dose (AEDO ) were detected based on the activity concentration of radionuclide in the tunnel. The annual effective dose was contributed from gamma radiation is 1.98 mSv that is lower than the recommended limit of 20 mSv, so no significant dose. While the public exposure for a long time for the extracted raw material can because a serious health effect. This is owing to the mean annual effective dose value (1.2 mSv) is a comparable to the recommended limit (1 mSv). Highlights: Natural radioactivity characterization of El-Missikat tunnel Egypt, was performed. Radiological hazard indexes were calculated and assessed the risk assessment. Significant natural radiation hazard comes from the studied granites.